IMPACT CURRENT RATIO, DEBT TO EQUITY, RETURN ON EQUITY AND GROWTH RATE ON DIVIDEN POLICY (Study the Mining Sector in 2016-2020 period) - Edeltrudis, Claudia; Liswati, Ilal; Samosir, Irfi Santa Uli; Ramadha, Fabian Rizky; Rahmawati, Anita; Yuliani, Reva (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aims to analyze the effect of Current Ratio(CR), Debt to Equity Ratio(DER),Return on Equity(ROE) and growth rate on dividend policy, both simultaneously and partially, as well as analyze the dominant variables that affect dividends. 2016 to 2020, with the object of research on mining companies listed on IDX. Research type descriptive with purposive sampling method. Based on the existing criteria, a sample of 16 companies was obtained. And the data analysis technique used multiple linear regression. The results showed that there was a simultaneous significant effect between the variables Current Ratio, Debt to Equity Ratio, Return on Equity and growth rate had a significant to dividenpayout.while partially only ROE and growth rate significant impact to dividenpayout.